2003
DOI: 10.1021/tx0340551
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Liver Microsomal (S)-Nicotine Oxidation by (−)-Menthol and Analogues

Abstract: (-)-Menthol is a widely used flavoring ingredient present in mouthwash, foods, toothpaste, and cigarettes; yet, the pharmacological effects of menthol have not been widely studied. Mentholated cigarette smoking may increase the risk for lung cancer. Many African American smokers smoke mentholated cigarettes, and African Americans have a significantly higher incidence of lung cancer as compared with whites. There may be a relationship between the incidence of lung cancer and the type of cigarette smoked because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 23 publications
4
51
0
1
Order By: Relevance
“…Menthol cigarette smoking has been associated with longer cotinine halflife in women (Ahijevych et al, 2002). Recently, a moderate inhibition of CYP2A6-mediated nicotine metabolism in human liver microsomes by menthol and various related compounds was reported (MacDougall et al, 2003). This is supported by a crossover study in people, showing that mentholated cigarette smoking significantly inhibits metabolism of nicotine to cotinine and nicotine glucuronidation when compared with smoking nonmentholated cigarettes (Benowitz et al, 2004a).…”
Section: G Factors Influencing Nicotine Metabolismmentioning
confidence: 97%
See 1 more Smart Citation
“…Menthol cigarette smoking has been associated with longer cotinine halflife in women (Ahijevych et al, 2002). Recently, a moderate inhibition of CYP2A6-mediated nicotine metabolism in human liver microsomes by menthol and various related compounds was reported (MacDougall et al, 2003). This is supported by a crossover study in people, showing that mentholated cigarette smoking significantly inhibits metabolism of nicotine to cotinine and nicotine glucuronidation when compared with smoking nonmentholated cigarettes (Benowitz et al, 2004a).…”
Section: G Factors Influencing Nicotine Metabolismmentioning
confidence: 97%
“…Inhibitors. Several compounds are inhibitors of CYP2A6-mediated nicotine metabolism in vitro, including methoxsalen (8-methoxypsoralen), tranylcypromine, tryptamine, coumarin, and neomenthyl thiol (Nakajima et al, 1996b;Zhang et al, 2001;Le Gal et al, 2003;MacDougall et al, 2003). Other inhibitors of coumarin 7-hydroxylation such as pilocarpine, metyrapone, R-(ϩ)-menthofuran, ␤-nicotyrine, naphthalene, 4,4Ј-dipyridyl disulfide, 2-(p-tolyl)-ethylamine, nootkatone, several azole antifungals, and rifampicin would also be expected to inhibit nicotine C-oxidation Tassaneeyakul et al, 2000;Fujita and Kamataki, 2001;Xia et al, 2002;Asikainen et al, 2003;Rahnasto et al, 2003;Denton et al, 2004).…”
Section: Nicotine Metabolismmentioning
confidence: 99%
“…Studies suggest that menthol inhibits the metabolism of nicotine in liver microsomal test systems 14 and influences the total metabolic clearance of nicotine. 15 Nicotine metabolism is primarily mediated by the enzyme cytochrome P450 2A6 (CYP2A6) in the liver.…”
Section: Nicotine Metabolism In Young Adult Daily Menthol and Nonmentmentioning
confidence: 99%
“…Previously, isoflavones (Nakajima et al, 2006), menthol (MacDougall et al, 2003;Kramlinger et al, 2012), menthofuran (Khojasteh-Bakht et al, 1998), isothiocyanates (Nakajima et al, 2001;von Weymarn et al, 2007), and several others (Di et al, 2009) were studied and found to inhibit CYP2A6. Based on the structural and biophysical studies of CYP2A6, low-molecular-weight phenylpropanoids, such as t-CA (Fig.…”
Section: Introductionmentioning
confidence: 99%